2014
DOI: 10.1515/corrrev-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibitors for metals in maintenance equipment: introduction and recent developments

Abstract: Corrosion inhibitors are extensively applied to prevent the corrosion of metals in maintenance and vehicles used by transportation agencies. The aim of this review is to examine the state of the corrosion inhibitors for the protection of various metals/alloys commonly used in maintenance equipment and vehicles and to identify cost-effective, high-performance corrosion inhibitors that may contribute to the preservation of equipment assets. The focus is placed on the metallic corrosion induced or aggravated by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Corrosion inhibitors are proven to be effective in reducing the metallic corrosion and thus preserving the service life and performance of assets (18). Furthermore, a recent study revealed that some agro-based inhibitors can offer additional benefits as "cryoprotectants," i.e., significantly lowering the freezing point of salt brine (19), which may translate to reduced salt application rates needed under cold weather scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion inhibitors are proven to be effective in reducing the metallic corrosion and thus preserving the service life and performance of assets (18). Furthermore, a recent study revealed that some agro-based inhibitors can offer additional benefits as "cryoprotectants," i.e., significantly lowering the freezing point of salt brine (19), which may translate to reduced salt application rates needed under cold weather scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the well-known corrosion inhibitors are organic compounds containing nitrogen, sulfur, or oxygen atoms (Cheng et al, 1999;Prabhu, Venkatesha, Shanbhag, Kulkarni, & Kalkhambkar, 2008;Samide, Bibicu, Rogalski, & Preda, 2004;Verma, Quraishi, & Ebenso, 2013;Wang, 2001). It has been found that most of the organic inhibitors act by adsorption on the metal surface (Abd El-Rehim, Ibrahim, & Khaled, 1999;Li et al, 2014). This phenomenon is influenced by the nature and surface charge of metal, by the type of aggressive electrolyte, and by the chemical structure of inhibitors (Thomas, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of corrosion inhibitors has been widely studied in the oil and gas production, and these experiments were normally conducted at low CO 2 partial pressure or other corrosive environments, which were summarized by Sim, Cole, Choi, and Birbilis (2014b) and Li et al (2014). However, investigations so far focusing on the effect of inhibitor on the corrosion behavior of steels under SC CO 2 conditions are very sparse.…”
Section: Effect Of Inhibitormentioning
confidence: 99%